Laparoscopic-assisted Approach to the Pelvic Flexure for Surgical Treatment of Sand Impaction in a Horse - Maia Teixeira, Pedro Paulo; Medeiros, Regina Mendes [UNESP]; Machado Silva, Marco Augusto; Coutinho, Leandro Nassar; Gomes Mariano, Renata Sitta [UNESP]; Vrisman, Dayane Priscila; Oliveira, Mariana Goncalves; Bonato, Denis Vinicius; Taira, Augusto Ryonosuke; Teobaldo Tironi, Stella Maris; Russiano Vicente, Wilter Ricardo [UNESP] (Univ Fed Rio Grande Do Sul, 2015)
Background: Laparoscopy provides good visualization of horse's abdominal cavity, besides providing minimal invasiveness and meticulous manipulation intra-abdominal organs. Laparoscopy is suitable for both diagnosing and treating acute abdomen in horses, The purpose of this study was to report a successful case of laparoscopic-assisted surgery for treating sand impaction in a horse. Case: A 3-year-old horse, weighing 460 kg, was admitted following chronic intermittent episodes of diarrhea and colic. Physical exam revealed mild abdominal pain and liquid/pasty diarrhea. There was negative survey of gastrointestinal hehninthes and microbiological analyses. Fecal sedimentation test revealed sand impaction. Surgical approach was opted for both accomplishment of the abdominal exploration and resolution of the impactation. The patient was anesthetized and positioned in dorsal recum.bency. Laparoscopy was performed through an 11.-mm trocar placed right cranially to the umbilicus. There were no apparent adhesions, bowel inflammation nor visceral displacement. A 15-cm celiotomy was carried out caudally to the umbilicus, under.laparoscopic guidance, for initial inspection of the gastrointestinal tract. Incision enlargement was required for exteriorizing the pelvic flexure, Afterwards, enterotomy was carried out for drainage of the impactating content, followed by enterorraphy. The pelvic flexure was rinsed with heparin diluted in normal saline (5 11.I/ ml) for prophylaxis of postoperative intraperitoneal adhesions. The pelvic flexure was repositioned within the abdominal cavity, followed by withdrawn of the trocar, synthesis of the muscle layer, approximation of the subcutaneous tissue and usual skin suture. Overall surgical time was 64 mm and the patient recovered uneventfully from anesthesia. Convalescence was excellent and the patient presented a short-term mild abdominal pain in the early postoperative period, using the visual analogue scale (VAS). The wound healed uneventfully following two weeks and no postoperative complication was noted. Discussion: Sand impaction a gastrointestinal disorder common in horses bred in sandy soil or subjected to poor quality water source, usually from streams or ponds. The aspect of the feces is an important parameter for the diagnosis, which is accomplished using the fecal sedimentation test. Intraperitoneal adhesions may affect the equine gastrointestinal tract following abdominal surgery or inflammatory disorders, with a predilection not only for anastomosis or enterotomy sites, hut also in cases of acute enteritis and impactations. Laparoscopy provided optimal observation of the abdominal cavity and close examination of the intestines for discharging the presence of inflammation-related intraperitoneal adhesions in this case. The laparoscopic-assisted approach to the pelvic flexure reduced the length of the surgical wound, while minimizing the likelihood of adhesion formation and preventing incision complications which are common complications following abdominal surgery in horses. The reduced cebotomy minimized postoperative pain, which has been one of the main efforts of surgeons for enhancing convalescence of patients undergoing exploratory celiotomy. The patient showed no relapsed or painful discomfort and had great recovery and healing, demonstrating that the technique can be applied in equine surgical clinic routine.
Keywords: endosurgery; video-assisted approach; colic; sediment; colt